Phylogenetic and phenotypic structure among Banksia communities in south-western Australia - Merwin, L.; He, Tianhua; Lamont, Byron (Blackwell Publishing, 2011)
Aim: Phylogenetic and phenotypic patterns among coexisting banksias (Banksia, Proteaceae) in the infertile, fire-prone landscapes of south-western Australia were examined for evidence of community structuring. It was expected that closely related species would be spatially clustered (underdispersed) as a consequence of widespread recent speciation, strong edaphic fidelity and low dispersability. We also expected that edaphic filtering would result in phenotypic clustering of traits related to habitat specialization and that competitive exclusion among closely related species with similar regeneration biology and growth form would result in phenotypic overdispersion of these latter traits. Location: Southwest Australian Floristic Region (SWAFR). Methods: Based on published data for coexistence (richness and frequency) of Banksia species at 40 sites in the three floristic provinces, phylogenetic, soil type and morphological mean pairwise distance and mean nearest taxon distance were calculated for each site and compared with null communities. Patterns of co-occurrence were examined at the local and subregional (provincial) scales.Results: Of the 40 sites assessed, 21-30 displayed phylogenetic clustering of Banksia species (5-11 significantly) such that, overall, co-occurring taxa were more closely related than expected by chance. Banksias in the Transitional Rainfall and Southeast Coastal Provinces were more likely to display phylogenetic clustering than in the High Rainfall Province. A significant trend for phylogenetic clustering associated with edaphic specialization (27-30 sites) was observed, as well as a significant trend for phenotypic overdispersion associated with growth form (25-28 sites). Results for regeneration biology depended on the metric used. Main conclusions: We demonstrate spatial clustering of closely related banksias at the local and provincial scales, consistent with their restricted distribution (recent widespread speciation, patchy habitat availability and limited dispersability) in this geologically old and stable region. The clustering of closely related species may also be a consequence of habitat filtering linked to edaphic fidelity in the SWAFR flora, while overdispersion in growth form suggests that functional divergence favours coexistence in Banksia communities.